Plasticized branched aliphatic oligoesters as potential mucoadhesive drug carriers - Snejdrova, Eva; Dittrich, Milan; Drastik, Martin (International journal of pharmaceutics, 2013)
Three oligoesters with different molar mass and degree of branching, intended as drug carriers, were synthesized and their thermal, rheological, adhesive, and drug release properties were studied. Triethyl citrate, ethyl pyruvate, ethyl salicylate, methyl salicylate, triacetin and tributyrin at a concentration of 20% were tested as plasticizers to improve drug incorporation, and application of the polymeric system. All of the tested plasticizers significantly depressed the Tg by at least 25.5°C. Plasticized oligoesters possessed remarkable adhesive properties on mucin in vitro, the adhesion is at least twofold bigger than it is for gels of cellulose derivatives. It was demonstrated that adhesivity increased with decreasing viscosity of oligoester matrices. In vitro dissolution tests of the flat matrices showed the prolongation of fluconazole release up to over 3 days for the oligoester carrier with the highest molar weight and degree of branching. Depending on the matrix hydrophilization, plasticizing led to an acceleration of the fluconazole release, the 3-h burst effect increased three times.
Keywords: Triethyl citrate (PubChem CID: 6506); Plasticizers; reologie; Dipentaerythritol (PubChem CID: 31352); Fluconazole; Glycolic acid (PubChem CID: 757); Mucoadhesion; Hydrophobic and Hydrophilic Interactions; viskozita; flukonazol; Drug Carriers; molekulová hmotnost; Drug release; Plasticizer; Methyl salicylate (PubChem CID: 4133); Molecular Weight; Viscosity; Rheology; Triacetin (PubChem CID: 5541); Branched polyesters; Fluconazole (PubChem CID: 3365); Lactic acid (PubChem CID: 612); Ethyl pyruvate (PubChem CID: 12041); polymery; Polymers; Adhesives; Esters; Tributyrin (PubChem CID: 6050); nosiče léků; Ethyl salicylate (PubChem CID: 8365); adheziva; hydrofobní a hydrofilní interakce; změkčovadla; estery